The Effect of The Implementation of Accounting Information Systems and Internal Control on Employee Performance - Ari Bramasto; Ridwan Hana Adiwiguna (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to determine the influence of application accounting Information system and internal control to employee performance at PT BPR Kerta Raharja Bandung Regency. This study using descriptive research methods and verification research methods. The sampling technique used was purposive sampling by determine appropriate specific criteria with the research. The statistic analysis used in this study is path analysis and hypothesis testing. The number of population in this study was 230 respondents with the sample used 48 employee PT BPR Kerta Raharja. Based on the research conducted, it can be seen that application of accouting system has no effect to employee performance but internal control has a significant effect on employee performance.